2019
DOI: 10.1111/aor.13525
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermic oxygenated machine perfusion alleviates liver injury in donation after circulatory death through activating autophagy in mice

Abstract: Hypothermic oxygenated machine perfusion (HOPE) is a safe and reliable method that could alleviate liver injury in donation after circulatory death (DCD). This study focuses on the role of autophagy in HOPE’s protective effect on DCD liver injury. A 30‐minute warm ischemic liver model was established in mice. After 4 hours of cold storage (CS), 1 hour of hypothermic machine perfusion (HMP) with 100% O2 or 100% N2 was employed. During 2 hours of reperfusion, liver tissue and perfusate were collected to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…It has been reported that programmed transient ischemia-reperfusion during shock, or during resuscitation also has protective effects [16]. Second, the protective effect of IPC is more prominent in primary hepatic I/RI in special cases, such as fatty and senile liver [10,13,29]. This study showed that RIPC-activated autophagy plays a role in hepatoprotection after hemorrhagic shock, but to what extent autophagy is the underlying mechanism and whether RIPC plays a more prominent role in special groups need further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that programmed transient ischemia-reperfusion during shock, or during resuscitation also has protective effects [16]. Second, the protective effect of IPC is more prominent in primary hepatic I/RI in special cases, such as fatty and senile liver [10,13,29]. This study showed that RIPC-activated autophagy plays a role in hepatoprotection after hemorrhagic shock, but to what extent autophagy is the underlying mechanism and whether RIPC plays a more prominent role in special groups need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy eliminates damaged organelles, increases ATP and amino acid levels to stabilize cell morphology, maintain function, or promote apoptosis [5][6][7]. Hepatocytes have an abundance of mitochondria and autophagy plays a crucial role in hepatic I/RI [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Xianpeng Zeng et al of Transplant Center of Wuhan University, Wuhan, China investigated the use of hypothermic oxygenated machine perfusion (HOPE) in liver donation after circulatory death (DCD) through activating autophagy in mice. A 30‐minute warm ischemic liver model was established.…”
Section: Transplantation and Organ Preservationmentioning
confidence: 99%
“…Hypothermic perfusion is successfully used for recovery of donor kidneys, particularly from extended criteria or DCDD donors with excellent results . Most kidney perfusion systems do not oxygenate the perfusate though this is essential to meet the metabolic demands for donor hearts.…”
Section: Machine Perfusion Preservation Strategiesmentioning
confidence: 99%
“…Hypothermic perfusion is successfully used for recovery of donor kidneys, particularly from extended criteria or DCDD donors with excellent results. [36][37][38][39] Most kidney perfusion systems do not oxygenate the perfusate though this is essential to meet the metabolic demands for donor hearts. Although an oxygen carrier, erythrocyte based or otherwise, 40,41 can be included in the preservation solution of cold perfused organs, dissolved oxygen in crystalloid solutions is sufficient to support myocardial oxidative metabolism.…”
Section: Hypothermic Machine Perfusion Preservationmentioning
confidence: 99%